Lorenzo Verderame & Agnès Garcia-Ventura, Receptions of the Ancient Near East in Popular Culture and Beyond. Atlanta, Lockwood Press. 2020. 319 pp. ISBN 978-1-948488-24-2. US$ 32.95. - Urbano, Luciana (2021)
Fil: Urbano, Luciana. Universidad Nacional de Rosario; Argentina